The Comparison Between Balinese and Singaporean Swear Words in Terms of References Used - Virginia, Puput; Budasi, I Gede; Suardana, Made (IJLHE: International Journal of Language, Humanities, and Education, 2026)
This study aims to compare the use of swear words in Balinese and Singaporean languages based on the references employed. This study applied a qualitative approach with a document study method, where data were obtained from relevant previous studies. The data were analyzed by classifying swear words into ten reference categories based on the framework of Malo and Adindarena (2021), which includes social conditions, concrete objects, abstract concepts, religion or supernatural beings, sexual organs or activities, body excretions, body parts, animals, actions, and professions. The results show that both languages have similarities in the use of universal references, such as social conditions and abstract concepts, to express negative evaluations and emotions. However, Balinese swear words show a wider variety of references through the presence of religious or supernatural, animals, concrete objects, and professions, which are not found in the Singaporean language. This difference reflects the influence of cultural values and social context on the selection of references in cross-cultural swear words. Also, this study contributes to sociolinguistics and discourse analysis by demonstrating that swear words can be systematically categorized through reference types.